Insulin protects against hepatocyte ultrastructural damage induced by type 1 diabetes mellitus in rats. (2nd November 2018) - Haidara, Mohamed A.; Dallak, Mohammad; El Karib, Abbas O.; Abd Ellatif, Mohamed; Eid, Refaat A.; Heidar, El Hassan A.; Al-Ani, Bahjat
ABSTRACT: Diabetic complications that affect vital organs such as the heart and liver represent a major public health concern. The potential protective effects of the hormone insulin against hepatocyte ultrastructural alterations induced secondary to type 1 diabetes mellitus (T1DM) in a rat model of the disease have not been investigated before. Therefore, rats were injected once with 65 mg/kg streptozotocin (T1DM group) and the protection group (T1DM+Ins) received a daily injection of insulin 48 h post diabetic induction by streptozotocin and continued until being sacrificed at week 8. The harvested liver tissues were examined using transmission electron microscopy (TEM) and blood samples were assayed for biomarkers of liver injury enzyme, glycemia, lipidemia, inflammation, and oxidative stress. TEM images showed that T1DM induced profound hepatocyte ultrastructural alterations as demonstrated by pyknotic nucleus, condensation of chromatin, irregular nuclear membrane, swollen mitochondria, dilated rough endoplasmic reticulum, damaged intercellular space, and accumulation of few lipid droplets inside the hepatocyte cytoplasm, which were substantially protected with insulin. In addition, the blood chemistry profile complements the TEM data as demonstrated by an increase in serum levels of alanine aminotransferase (ALT), dyslipidemia, C-reactive protein (CRP), tumor necrosis factor-alpha (TNF-α), interleukin-6 (IL-6), and malondialdehyde (MDA) by T1DM that were significantly ( p < 0.05) reduced with insulin injections. Thus, we conclude that insulin effectively protects against T1DM-induced liver injury in rats for a period of 8 weeks, possibly due to the inhibition of inflammation, oxidative stress, and dyslipidemia.